A Cross-Cultural Study of Gifted Students' Scientific, Societal, and Moral Questions Concerning Science. (29th August 2012) - Tirri, Kirsi; Tolppanen, Sakari; Aksela, Maija; Kuusisto, Elina
Abstract : This study investigated the number and nature of gifted female and male students' scientific, societal, and moral questions concerning science. The participants (N = 658 ) of this study were 16–19-year-old international students from 55 countries and two continents, Asia and Europe. They applied to participate in the Millennium Youth Camp held in 2011 in Finland. The students came from scientifically and mathematically oriented schools, and they had shown an interest towards science through competitions, school success, and their own research. The students were asked to formulate questions they would like to get answers to during the camp. The nature and number of the students' questions were analyzed with qualitative and quantitative content analysis. The results showed that the boys asked more scientific questions than the girls, and the girls asked more societal questions than the boys. The students asked less questions about morality than scientific or societal questions. The most common questions about morality were related to pollution and fresh air, environmental problems, and water protection. The results point to the need for teachers to teach socioscientific issues and discuss moral questions related to science.